Cell-free nucleic acids as noninvasive biomarkers for colorectal cancer detection - Mansour, Hicham (Frontiers in Genetics, 2014)
Cell-free nucleic acids (CFNA) have been reported by several authors in blood, stool and urine of patients with colorectal cancer (CRC). These genetic biomarkers can be an indication of neoplastic colorectal epithelial cells, so they can potentially be used as noninvasive tests for the detection of the disease in CRC patients and monitor their staging, without the need to use heavier and invasive tools. In a number of test-trials, these genetic tests have shown the advantage of non-invasiveness, making them well accepted by most of the patients, without major side effects. They have also shown a promising sensitivity and specificity in the detection of malignant and premalignant neoplasms. Moreover, costs for performing such tests can be very low. Several studies reported and confirmed the proof of the principle for these genetic tests for screening, diagnosis and prognosis; the main challenge of translating this approach from research to clinical laboratory is the validation in large and long-term randomized trials to prove sustainable high sensitivity and specificity. In this paper, we present a review on the noninvasive genetics biomarkers for CRC detection described in the literature and the challenges that can be encountered for validation processes.